2005
DOI: 10.1175/jpo2762.1
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Amplitude Evolution of Instabilities Associated with the Coastal Upwelling Front

Abstract: A primitive equation model is used to study the finite-amplitude evolution of instabilities associated with the coastal upwelling front. Simulations of increasing complexity are examined that represent idealizations of summer conditions off the Oregon coast, including cases with steady and with time-variable wind in a domain with alongshore-uniform bathymetry and with time-variable wind in a domain with realistic Oregon coast bathymetry. The numerical results indicate that the fastest-growing mode in this syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 21 publications
10
47
1
Order By: Relevance
“…Baroclinic instability can then release this available energy into an eddy field that has a scale of the baroclinic radius of deformation, that is, of O(5-10) km over stratified midlatitude shelves. One aspect, involving wind-driven upwelling fronts, of this conjecture is already well studied and well accepted (e.g., Barth 1989a,b;Barth 1994;Durski and Allen 2005;Durski et al 2007). These fronts tend to be unmistakably intense and dramatic, and so FIG.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Baroclinic instability can then release this available energy into an eddy field that has a scale of the baroclinic radius of deformation, that is, of O(5-10) km over stratified midlatitude shelves. One aspect, involving wind-driven upwelling fronts, of this conjecture is already well studied and well accepted (e.g., Barth 1989a,b;Barth 1994;Durski and Allen 2005;Durski et al 2007). These fronts tend to be unmistakably intense and dramatic, and so FIG.…”
Section: Introductionmentioning
confidence: 88%
“…Another possibility is that the eddy field is associated with flow over irregular topography, although the smaller-scale eddy field is evidently found over locations with both relatively rough (e.g., northern California; Dever 1997) and smooth (Middle Atlantic Bight; S. Lentz 2015, personal communication) topography. Further, Durski and Allen (2005) show, for conditions representative of the Oregon shelf, that irregular topography complicates the eddy field associated with a shelf baroclinic instability, but it does not supersede it. Nonetheless, this possibility will be considered in a future publication.…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, submesoscale upwelling filaments can enhance the off-shelf flux of labile DOM (Alvarez-Salgado et al, 2001). Vertical velocities are higher at submesoscale density fronts (Klein and Lapeyre, 2009;Levy et al, 2012;Thomas et al, 2008), which are prominent features in eastern boundary upwelling systems (Durski and Allen, 2005). These vertical velocities often extend to below the mixed layer (Klein et al, 2008), where they can drive sizeable vertical fluxes of solutes.…”
Section: Physical Fluxes Of Dommentioning
confidence: 99%
“…This instability would occur because alongshore winds drive either upwelling or downwelling circulations that, in turn, tilt isopycnals and so create available potential energy (APE). This idea is not entirely new; it has been shown that coastal upwelling fronts are expected to be unstable (Barth 1989a,b;Barth 1994;Durski and Allen 2005;and others), but this is a particularly energetic extreme of wind forcing, and the statistical properties of the resulting eddies have not received much attention. On the other hand, there is very little in the literature involving realistic downwelling configurations over the shelf.…”
Section: Introductionmentioning
confidence: 99%
“…More realistic, broadband wind forcing is the subject of an ongoing study, which will be reported as the third part of the present sequence in the near future. It is worth noting that Durski and Allen (2005) briefly consider time-variable alongshore winds, but they do not include frequent reversals. One might expect potentially different results with reversing winds because alternating upwelling and downwelling would presumably cause the available potential energy required for baroclinic instability to vary radically with time.…”
Section: Introductionmentioning
confidence: 99%